Position sensing of jetting droplets enabled by triboelectric nanogenerators. (May 2023) - Hu, Songtao; Ding, Xijia; Fan, Beibei; Zhang, Chi; Zhang, Bo; Shi, Xi; Peng, Zhike
Abstract: Inkjet printing, as a drop deposition technique, has been the subject of considerable scientific research and technological application; however, deposition positioning is typically realized by imaging techniques and its in-situ monitoring remains elusive. Here, we report a solid-liquid triboelectric nanogenerator (TENG) sensing technique for the position sensing of jetting droplets. Four single-electrode-mode TENG units cooperate to assemble a self-aware array to achieve droplet positioning based on the triboelectric output sum and ratio. The demonstration of the technique shows that the open-circuit voltage can be regarded as the key index to precisely characterize the deposition positioning of jetting droplets. The voltage-position characteristic curve is well explained by developing an equivalent-capacitor-set hypothesis, expressing the relationship between voltage and contact area. Moreover, we extend the work from one-dimensional to two-dimensional position sensing and develop an intelligent software platform for visualization, showing high accuracy with the maximum error of 0.164 mm. We believe this study to be the very first demonstration of solid-liquid TENGs for the position sensing of inkjet printing, paving the way for in-situ monitoring of intelligent devices such as additive manufacturing. Graphical Abstract: ga1 Highlights: TENGs are introduced into the field of inkjet printing. A solid-liquid TENG sensing technique for the positioning of jetting droplets is proposed. The sensing mechanism is revealed by developing an equivalent-capacitor-set hypothesis. The solid-liquid TENG sensor paves the way for in-situ monitoring of intelligent devices.